2007
DOI: 10.1007/s00380-006-0955-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interferon-g and interleukin-4 production in CD4+ T cells in patients with chronic heart failure

Abstract: The prevalence of inflammation is high among patients with chronic heart failure (CHF). Reduced ejection fraction was associated with frequency of CD4(+) T cells of leukocytes. Therefore, we investigated inflammatory cytokines of expression markers in CD4(+) T cells in patients with CHF. Blood samples were obtained from 103 patients with CHF, from 83 patients with stable angina (SA), and from 57 controls. Interferon-gamma (IFN-gamma)-positive CD4(+) T cells and interleukin-4 (IL-4)-positive CD4(+) T cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…IFN-γ is an important pro-inflammatory cytokine produced by Th1 cells, that increases the expression of MHC class I and class II molecules. An increase in the percentage of IFN-γ-positive CD4 (+) T cells, has previously been described in patients with CHF [30]. Furthermore, an increase in IFN γ serum levels has also been described [31], in a mouse model, one week after MI, i.e.…”
Section: Discussionmentioning
confidence: 88%
“…IFN-γ is an important pro-inflammatory cytokine produced by Th1 cells, that increases the expression of MHC class I and class II molecules. An increase in the percentage of IFN-γ-positive CD4 (+) T cells, has previously been described in patients with CHF [30]. Furthermore, an increase in IFN γ serum levels has also been described [31], in a mouse model, one week after MI, i.e.…”
Section: Discussionmentioning
confidence: 88%
“…These results are in agreement with observations made in clinical studies describing a positive correlation between T-cell polarization to Th1 and left ventricular dysfunction in patients with HF. 6,23 To date, the relationship between T-cell activation and the development of chronic HF has been poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, the percentage of circulating CD4 + T cells expressing inflammatory cytokines was positively correlated with left ventricular dysfunction in patients with HF. 6,7 However, the significance of these observations and the contribution of T cells to cardiovascular remodeling are still poorly understood.…”
Section: Clinical Perspective On P 2124mentioning
confidence: 99%
“…Several authors have explored the role of immune components in CHF and reported activation of the adaptive immune system, more specifically T cells. For example, the number of circulating interferon (IFN)‐γ+ CD4 T cells is increased in patients with CHF (determined by impaired left ventricular ejection fraction, LVEF) [3]. These cells represent Th1 CD4 T cells, which constitutively display an inflammatory phenotype.…”
Section: Introductionmentioning
confidence: 89%